Dever de casa e desempenho acadêmico na disciplina matemática das 3ª e 4ª séries do Ensino Fundamental - Rodrigues, Rose Mary Guimarães (1996)
This research, with ethnographic characteristics, aimed to show the relationship between homework and excellent, good / very good and poor academic achievement in mathematics, using direct observation in the classroom and interview, as data collection methods. The observed sample consisted of 102 students and three teachers from four classrooms, one from the third and three from the fourth grade of elementary school randomly chosen by lot. The semi-structured interview was conducted with 22 students from this sample, their math teachers, their parents and the principal of the school of the Federal School of Uberlândia, Minas Gerais, Brazil. The data obtained showed that the student considered excellent by the teacher, as well as the one classified as good and very good, often performs more complete homework than the student considered as weak. It was also evidenced the relevance of the actions of the teachers when the task was requested and corrected, and of the parents, during the performance of the same. Likewise, the time spent on TV can influence the student's academic performance. . The analysis of the teacher's previous and consequent actions of the homework indicated the importance that the teacher gives to this activity as parents and students recognize, in turn, the importance of the homework, although the latter do not like it very much. to do it, especially in large quantities. Parental action was also analyzed in terms of how they monitor their child, including the arrangement of the home environment, control of television and other hours, and it appears that one can conclude. that they still need more information about how to help their children with their schoolwork, so that they can contribute to their better results in their academic performance. The author hopes that the information collected will be useful to all those who in one way or another are directly or indirectly involved with homework, as it seems to be extremely useful for student learning, if well worked at school, at home and by the student himself.